(untitled) (Bangladesh Journal of Plant Taxonomy, 2012)
Lloydia nana R. Li & H. Li, a new species of Liliaceae from eastern Xizang, China, is described and illustrated. Morphologically, it is closely similar to L. serotina var. parva (C. Marquand & Airy Shaw) H. Hara and L. yunnanensis Franchet, but differs from the former by having single basal leaf, taller stigma than anthers; from the latter by having dwarf habit 2.5-4.0 cm tall, indistinctly 3-lobed stigma, and style slightly longer than ovary. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10939 Bangladesh J. Plant Taxon. 19(1): 33-36, 2012 (June)